A cohort study of women with a Fontan circulation undergoing preconception counselling. Issue 7 (19th January 2016) - Cauldwell, Matthew; Von Klemperer, Kate; Uebing, Anselm; Swan, Lorna; Steer, Philip J; Babu-Narayan, Sonya V; Gatzoulis, Michael A; Johnson, Mark R
Abstract : Objective: To describe outcomes for women with a Fontan circulation attending preconception counselling (PCC). Exploring (1) impact of counselling on decision to become pregnant; (2) pregnancy rates in those opting for pregnancy and (3) short-term and long-term outcome of those who succeeded in becoming pregnant. Methods: Retrospective review of women aged 16–45 years with a Fontan circulation from 1994 to 2014. Results: 58 women were offered PCC, 3 declined and 55 received PCC. Following PCC, 15 opted against conception, 16 decided to delay pregnancy, 19 attempted pregnancy and 5 were lost to follow-up. Of the 19 women, 14 succeeded, becoming pregnant a total of 43 times (median 1, range 1–9). Of these, 6 miscarried all pregnancies. 8 carried 14 pregnancies to viability. Baseline hypoxaemia and cardiac disease in pregnancy (CARPREG) score was similar in those opting for and against pregnancy, but CARPREG score was better in those delaying conception. Women exclusively miscarrying or unable to conceive were more likely to have baseline hypoxaemia and greater CARPREG score. Cardiac complications included arrhythmia requiring treatment (n=4) and one thromboembolism. Obstetric complications were greater in women with a Fontan circulation, 10 preterm births (<37 weeks) and 8 small for gestational age babies (<10th centile). There was one neonatal death. At follow-up, there was no deterioration in clinical status as determined by echo. Conclusions: Most women accept PCC and decided to pursue pregnancy; in some cases, this was despite being advised of a poor prognosis. Pregnancy outcome was related to baseline hypoxia and CARPREG scores.